Mediating Effect of the Knowledge Management on Organisational Performance - kadiri, kayode ibrahim (EduPsyCouns: Journal of Education, Psychology and Counseling, 2024)
The study assessed the mediating effect of the of knowledge management on performance of listed food and beverages companies in Lagos state, Nigeria. The study adopted the survey research deign, the population consists of 820 top and middle level staff of selected food and beverage firms (Nestle Nigeria Plc, Unilever Nigeria Plc and Honeywell Flour Mill), in Lagos State, Nigeria. Purposeful sampling technique was adopted for this study. The study employed Taro Yamane (1967) formula for determining the minimum sample size. Therefore, 267 were the sample size for this study. The study utilize primary source of data to collect data for the study. To ensure content validity and instrument reliability, the study underwent a pilot test. The study adopts quantitative method to analyze and statistically present and test the data that were collected. Findings from the analysis indicate that the model is adequately fit to measure the relationship between knowledge management and performance of food and beverages companies. First finding revealed that knowledge acquisition has a positive and insignificant effect on performance, second finding revealed that knowledge application has a positive and significant effect on performance, The study recommends that food and beverages companies should encourage their employees to engage in continuous learning and provide them with opportunities to acquire new knowledge and skills, Food and beverages companies should also place emphasis on knowledge sharing of their employees, especially through on-the-job training styles such as job rotation